Pengaruh Price discount dan E-Word of Mouth Terhadap Purchase Decision Tiket Bioskop Melalui M-TIX - Bella Kalyana Putri; Devianti Nurazizah; Rifki Munawar; Ramayani Yusuf (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study was to determine how Price discount and Electronic Word Of Mouth influence the Purchase Decision of Cinema Tickets through M-TIX. This study uses a descriptive type of analysis with quantitative methods. The entire Garut community became the population in this study, while 100 respondents became the sample. Saturated samples were used in this study. The data was collected using a questionnaire and analyzed using SPSS multiple regression analysis on Windows 25.0. The results showed that Price discount and E-Word Of Mouth can explain the Purchase Decision variable by 73.3%, while the remaining 26.7% is explained by other variables not included in the model.